KEPEMILIKAN INSTITUSIONAL SEBAGAI PEMONITOR MANAJEMEN LABA MELALUI PEMILIHAN AUDITOR BERKUALITAS - Endang Raino Wirjono (KINERJA, 2005)
The objective of this study is to investigate the impact of institutional investors and auditquality (measured by industry market share) on earnings management (measured by discretionary accruals). Empirical researches provide evidence that firms execute income increasing or decreasing discretionary accruals in financial statement. To test alternative hypothesis, the study uses manufacturing companies listed in the Jakarta Stock Exchange during 2000-2002. There are 88 samples, which are collected from manufacturing companies. Results of this study indicated that institutional investors have significant impact on earnings management. However, this study can not support that auditor quality have interaction effect on the relationship between institutional investors and earnings managementKeywords: institutional investors, earnings management, audit quality